2003
DOI: 10.1080/0307945031000097859
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a new tetravalent coryza vaccine against emerging variant type B strains

Abstract: Outbreaks of infectious coryza have been reported in vaccinated flocks in different countries, indicating that new serotype(s) of Haemophilus paragallinarum may have evolved. Several field isolates from vaccinated flocks in the US, Ecuador, Argentina and Zimbabwe were examined and, apart from one serotype C strain, all were typed as serotype B. An inactivated commercial trivalent vaccine, containing serotypes A, B and C, protected against challenge with the serotype C isolate but protection against challenge w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 1 publication
3
19
0
Order By: Relevance
“…This evidence of antigenic diversity within Page serovar B/Kume serogroup B is further supported by the recent report that a standard commercial A, B, C trivalent infectious coryza vaccine provided a weaker level of protection against so-called 'variant' Page serovar B field isolates (Jacobs et al, 2003). Indeed, Jacobs et al (2003) reported that the inclusion of one of the 'variant' Page serovar B isolates, resulting in a tetravalent vaccine, was necessary to achieve good protection.…”
Section: Discussionsupporting
confidence: 54%
“…This evidence of antigenic diversity within Page serovar B/Kume serogroup B is further supported by the recent report that a standard commercial A, B, C trivalent infectious coryza vaccine provided a weaker level of protection against so-called 'variant' Page serovar B field isolates (Jacobs et al, 2003). Indeed, Jacobs et al (2003) reported that the inclusion of one of the 'variant' Page serovar B isolates, resulting in a tetravalent vaccine, was necessary to achieve good protection.…”
Section: Discussionsupporting
confidence: 54%
“…Naturally male chickens are more susceptible too A. paragallinarum than females [38]. The present study result was in line with this fat in that the prevalence was 30.2% in males and 20.5% in females.…”
Section: Discussionsupporting
confidence: 79%
“…Erythromycin, Tetracycline, Fluoroquinolones, Sulphadimetoxine, and Sulphamethazine can be used as treatment medication. Although treatment may result in improvement, the disease may recur when medication is discontinued [3,12,[21][22][23][24]38].…”
Section: Treatmentmentioning
confidence: 99%
“…As all controls were fully susceptible to challenge and as no antibodies to infectious coryza were detected in any chicken prior to vaccination, there is good evidence that the chickens used in this work were fully susceptible to infectious coryza. Our use of commercial chickens is a practice that has been adopted by other infectious coryza vaccine researchers (Terzolo et al, 1997;Jacobs et al, 2003;Bragg, 2004;Soriano et al, 2004).…”
Section: Methodsmentioning
confidence: 99%